Morte e rinascita di una risorsa sostenibile: le terre d’acqua e il riso Gigante Vercelli - Davide Porporato (Archivio Antropologico Mediterraneo)
This essay provides a first insight on the recently resumed production of the “Gigante (Giant) Vercelli”, a rice cultivar created in 1936, but whose production had ceased in the 1960s. We conducted our survey in the Vercelli area, the heart of one of the largest Italian agro-industrial districts. Today the cultivation of this variety of rice, which has a peculiar, natural resilience to rice blast, the most serious fungal disease on the planet, is possible everywhere, but its growing areal is limited to Piedmont. In 2018, the Slow Food “Gigante Vercelli” rice presidium was established, with a product specification highly attentive to sustainability issues.